1958
DOI: 10.1039/tf9585400250
|View full text |Cite
|
Sign up to set email alerts
|

The adsorption of water by Saran charcoal

Abstract: Equilibrium isotherms for water have been measured on three samples of Saran charcoal between 10" C and 60" C. The heats of adsorption at very low surface coverage are as high as 15,000 callmole, but for most of the water adsorbed are only slightly greater than the heat of liquefaction. On desorption, there is no hysteresis loop.Water adsorbs more slowly than a hydrocarbon of comparable size. At low relative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1962
1962
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…The isotherms for these samples are type-I patterns, which is typical of microporous solids (Figure S1 A). [10] MC andS O 3 H-MC have similar isotherms to that of the Y-zeolite, suggesting that the microporous structure formed in the sulfonated samples also reflects the originalYzeolite structure. The BET surface area of SO 3 H-MC was estimated to be % 2000 m 2 g…”
Section: Resultsmentioning
confidence: 59%
“…The isotherms for these samples are type-I patterns, which is typical of microporous solids (Figure S1 A). [10] MC andS O 3 H-MC have similar isotherms to that of the Y-zeolite, suggesting that the microporous structure formed in the sulfonated samples also reflects the originalYzeolite structure. The BET surface area of SO 3 H-MC was estimated to be % 2000 m 2 g…”
Section: Resultsmentioning
confidence: 59%
“…The surface of the graphite is generally hydrophobic, [14] and, therefore, the H 2 O vapor adsorption-desorption isotherm of pure graphitic carbon at 328 K had a well-defined type-III character, for which the amount of adsorbed H 2 O was small at low P/P 0 (< 0.2) and steeply increased at P/P 0 = 0.5-0.6. [15] The strong affinity of CCSA-673 and 723 for H 2 O is clearly derived from the large amounts of hydrophilic functional groups. The hysteresis loop in the isotherms of CCSA-673 and 723 also supported the strong affinity for water.…”
mentioning
confidence: 99%
“…Earlier studies [33,[41][42][43][44] have reported information on the shapes of water vapour adsorption isotherms for chars, which are in general different in comparison with activated carbons. Investigations by Dacey et al [41,42] on the adsorption of water vapour by Saran charcoal at different temperatures reported well-defined isotherms of type V with a steep increase at a medium relative pressure (p/p 0 ≈ 0.5-0.6).…”
Section: Shape Of the Adsorption Isothermsmentioning
confidence: 98%